2008
DOI: 10.1039/b719335a
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced changes in photosystem I activity as measured with different electron donors in isolated spinach thylakoid membranes

Abstract: Heat-induced changes in photosystem I (PSI) have been studied in terms of rates of oxygen consumption using various donors (DCPIPH2, TMPDred and DADred), formation of photo-oxidized P700 and changes in Chl a fluorescence emission at 77 K. Linear heating of thylakoid membranes from 35 degrees C to 70 degrees C caused an enhancement in PSI-mediated electron transfer rates (DCPIPH2-->MV) up to 55 degrees C. However, no change was observed in PSI rates when other electron donors were used (TMPDred and DADred). Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To examine the degrees of denaturation at the extracellular domains of PSI and PSII, such as the [4Fe-4S] clusters F a and F b in PsaE for PSI and the oxygen-evolution complex (OEC) for PSII, we examined the light-induced electron transfer activities of PSI and PSII and the lifetimes of the charge-separated state at the special pairs P700 of PSI. The light-induced electron transfer activities of PSI and PSII can be estimated by the rates of O 2 consumption and O 2 evolution using an O 2 electrode, respectively. ,− The lifetime of P700 +• can be estimated from a nonlinear curve-fitting analysis of the time-course decay in A 689 after a pulse of photo excitation at 400 nm . The elimination or damage to PsaE, including the [4Fe-4S] clusters F a and F b , shortens the lifetime of P700 +• to 1 ms, instead of 30 ms (on native state).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the degrees of denaturation at the extracellular domains of PSI and PSII, such as the [4Fe-4S] clusters F a and F b in PsaE for PSI and the oxygen-evolution complex (OEC) for PSII, we examined the light-induced electron transfer activities of PSI and PSII and the lifetimes of the charge-separated state at the special pairs P700 of PSI. The light-induced electron transfer activities of PSI and PSII can be estimated by the rates of O 2 consumption and O 2 evolution using an O 2 electrode, respectively. ,− The lifetime of P700 +• can be estimated from a nonlinear curve-fitting analysis of the time-course decay in A 689 after a pulse of photo excitation at 400 nm . The elimination or damage to PsaE, including the [4Fe-4S] clusters F a and F b , shortens the lifetime of P700 +• to 1 ms, instead of 30 ms (on native state).…”
Section: Resultsmentioning
confidence: 99%
“…Although the heat stress has the negative effects on PSI (Tiwari et al 2008(Tiwari et al , Živčák et al 2015 or other components of ETC, the effects of high temperature on PSII are the most prominent. It is well known that the oxygenevolving complex is one of the most sensitive components of PSII, which is reflected also at the level of OJIP kinetics (Srivastava et al 1997, Mathur et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier results (Tiwari et al 2008) have shown that F 685 decreased with increasing temperature while F 730 is largely unaffected. Thus, although the ratio (F 730 /F 685 ) increased, no energy transfer at the expense of PS 2 took place at high temperature.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 87%